Environmental Justice for the Bantar Gebang Scavenger Community - Zuhriyah, Aminah; Pudjiastuti, Sri Rahayu (Yayasan Ilomata, 2024)
The Bantar Gebang landfill is a paradise for scavengers. However, this condition is inversely proportional to the reality of an unhealthy environment and increasing poverty. On this basis, this research aims to examine the extent of environmental justice for this community. This research uses qualitative techniques with a case study approach starting from 2022-2023 with informants from Bantar Gebang scavenger residents and the Bantar Gebang TPST. It was found that environmental justice was not yet running as it should, and this was further exacerbated by the lack of public education, and the lack of optimal attention from the local government. Thus, the urgency of environmental justice at the grassroots supports sustainable development, especially for the welfare of scavengers with the principle of equality. The government should be able to change its perspective in paying attention to the living conditions of these minorities with a social empathy approach that is included in environmental regulations by giving them the right to participate in making decisions.